Polyetheretherketone (PEEK) for making bone implants in maxillofacial reconstruction surgery - Anwar S. Ibrahim; Cholid Badri; Benny S. Latief; Sastra K. Wijaya; V. Sutarmo Setiadji; Agri Suwandi (AITI, 2017)
Polyetheretherketone (P.EEK) has been used as a bone implant because it has the nature of a biocompatible, strong, non-corrosive, stable and not affected by high temperatures. PEEK is potential for use as an implant material. Applications in maxillofacial reconstruction surgery is very beneficial in terms of time and cost. Modelmaking mandible obtained from data on patients affected by tumor ameloblstoma. The data have been taken by a CT-scan in the form of DICOM (Digital Imaging and Communication in Medicine) is amended by Catya into STL files (stereolithography). STL file is then printed with 3D-printers and Computer Numerical Control (CNC) machines.Printouts based models have been created for the reconstruction implants in maxillofacial surgery.